8x+6=9x-9

Simple and best practice solution for 8x+6=9x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+6=9x-9 equation:


Simplifying
8x + 6 = 9x + -9

Reorder the terms:
6 + 8x = 9x + -9

Reorder the terms:
6 + 8x = -9 + 9x

Solving
6 + 8x = -9 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
6 + 8x + -9x = -9 + 9x + -9x

Combine like terms: 8x + -9x = -1x
6 + -1x = -9 + 9x + -9x

Combine like terms: 9x + -9x = 0
6 + -1x = -9 + 0
6 + -1x = -9

Add '-6' to each side of the equation.
6 + -6 + -1x = -9 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = -9 + -6
-1x = -9 + -6

Combine like terms: -9 + -6 = -15
-1x = -15

Divide each side by '-1'.
x = 15

Simplifying
x = 15

See similar equations:

| 5x-9=4x-13 | | z-5.2=17.8 | | 3x(x-1)-24=2x^2+x^2+3x | | -4x-7+10x=-7+6z | | 8+9x-7(5x-7)=8x | | 10y^6/2y^2 | | 8(s-10)=132 | | T+8=4t-7 | | x(.25)+y(.10)=6.05 | | -(x-1)/57 | | 6w+5y+8x+7x+-12y+4w= | | 3x-12=4-5x | | 1-7b=-3 | | xf(y)+yf(x)=(x+y)*f(x)*f(y) | | 2x+7=14x-41 | | |x|/4=5 | | f(x)=-.67x^2+8x+24 | | 16x+12=-1+17x | | xf(y)+yf(x)=(x+y)f(x)f(y) | | x-(x*0.1957)-64.84=400 | | -15x+18=10x | | 11x-12+60=180 | | 2/9x=14 | | 14/-2/-18=24 | | 5x^5=-24 | | (2/3)/(-7/3) | | -5x=(-2x)+(-4) | | 12/11@=p/12 | | 5(10x-10)=-5-6x | | 15ml/x=5ml/75mg | | 8x^2-35x+33=0 | | 6x-4.50= |

Equations solver categories